2021
DOI: 10.1186/s12942-021-00280-2
|View full text |Cite
|
Sign up to set email alerts
|

Parent’s sociodemographic factors, physical activity and active commuting are predictors of independent mobility to school

Abstract: Background Independent mobility (IM) provides young people with many opportunities to increase their autonomy and physical activity (PA). This study aimed to analyse whether the parent’s PA, active commuting to work and sociodemographic factors serve as predictors of IM to school in children and adolescents. Methods A total of 684 parents (52.8% mothers) and their offspring (56.4% girls) were included in this study, which was performed in Granada (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Different levels of physical activity were found in urban and rural adults of various socioeconomic backgrounds in the United States [4], which may be due to favorable infrastructure, accessibility to sports or recreational facilities, or a history of long-term exercise promotion. In addition, parents' physical activity, active commuting to work, and sociodemographic factors served as predictors of individual commuting to school [42]. These are not totally unsupported in the current study, such as patents' educational qualifications, occupations, and the size of their families of socio-demographic factors.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Different levels of physical activity were found in urban and rural adults of various socioeconomic backgrounds in the United States [4], which may be due to favorable infrastructure, accessibility to sports or recreational facilities, or a history of long-term exercise promotion. In addition, parents' physical activity, active commuting to work, and sociodemographic factors served as predictors of individual commuting to school [42]. These are not totally unsupported in the current study, such as patents' educational qualifications, occupations, and the size of their families of socio-demographic factors.…”
Section: Discussionmentioning
confidence: 76%
“…Existing literature also supports this finding. The university students who lived in lower-SES neighborhoods reported more active commuting to university trips per week than those who lived in higher-SES neighborhoods [45], and the issue is connected to the parents' income level [42].…”
Section: Discussionmentioning
confidence: 98%
“…The lower access and availability of low-income families to motorized vehicles could justify the greater realization of more active journeys by children to school (Silva et al, 2018). In addition, making active trips to school depends in part on the independent mobility of schoolchildren, being higher in those families with lower income and lack of available vehicles to accompany their children to school (Larouche et al, 2020;Rodríguez-Rodríguez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in different countries identified potential factors associated with PAL and physical activity behaviors of adolescents considering individual, interpersonal, and environmental influences [ 10 ]. A recent review has pointed out that several factors including age, gender, parent activity level, physical activity and sport participation in school, peer support, and socioeconomic status could affect the PAL of adolescents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review has pointed out that several factors including age, gender, parent activity level, physical activity and sport participation in school, peer support, and socioeconomic status could affect the PAL of adolescents [ 11 ]. Moreover, PAL has been reported to be linked with screen time of adolescents [ 12 ], choice of school transportation [ 10 ], and condition of school environment [ 13 ]. Since regional and cultural differences is an important determinant associated with PAL [ 14 ], identifying the factors related with PAL and physical activity behavior of Turkish adolescents in order to plan and implement national public health policies is warranted.…”
Section: Introductionmentioning
confidence: 99%